Ethylene Signaling Facilitates Plant Adaption to Physical Barriers - Liu, Simu; Chen, Hui (Frontiers in Plant Science, 2021)
Morphological changes are usually used by terrestrial plants to respond to physical barriers. The phytohormone ethylene plays an essential role in exogenous mechanical impedance-triggered plant morphological development, which enables plants to grow optimally in response to physical barriers. Ethylene is shown to regulate these developmental processes directly or in concert with other phytohormones, especially auxin. Here, the involvement of ethylene action in seedling emergence from the soil, root movement within the soil, and parasitic plant invasion of host plant are described.